THE ACQUISITION CONTROL AND SENDING DATA SYSTEM OF AT89S52 AS PART OF TRAFFIC CONGESTION INFORMATION SYSTEM - Mulia, Tony; da Silva, Bernardus E.F.; Arfiansyah, Arfiansyah (Majalah Ilmiah Matematika Komputer, 2006)
Real time data communication between personal computer (PC) and microcontroller AT89S52 via commercial telephone line as a part of the traffic information system has been build and tested which yield a good result. The raw input data from Passive Infra Red (PIR) sensor of traffic condition was processed by microcontroller to be Dual Tone Multi Frequency (DTMF) tone code then send to PC via commercial telephone network. The PC will process the data to become a useful information of traffic condition and display it on the monitor. The microcontroller AT89S52 also control the timing of data collection from PIR sensor and maintaining status check with the PC.